Characterization of a new miniCAST with diffusion flame and premixed flame options: Generation of particles with high EC content in the size range 30 nm to 200 nm. Issue 1 (2nd January 2019) - Ess, Michaela N.; Vasilatou, Konstantina
Abstract: Flame-generated soot from miniCAST burners is increasingly being used in academia and industry as engine exhaust soot surrogate for atmospheric studies and instrument calibration. Previous studies have found that elemental carbon (EC) content of miniCAST soot is proportional to the mean particle size. Here, the characterization of a prototype miniCAST generator (5201 Type BC), which was designed to decouple the soot composition from the particle size and produce soot particles with high EC and BC content in a large size range, is reported. This prototype may operate either in a diffusion-flame or a partially premixed-flame mode, an option that was not available in former models. It was confirmed that soot properties, such as EC content and Ångström absorption exponent ( AAE ), were linked to the overall flame composition. In particular, combustion under fuel-rich conditions provided particles with size coupled to the EC fraction and AAE, i.e. smaller particles exhibited a lower EC fraction and higher AAE . In contrast, with fuel-lean diffusion flames and especially with premixed flames under near overall stoichiometric conditions small particles (down to 30 nm) with high EC/TC ratios (>60%) and low AAE (≈1.4) could be generated even without any thermal after-treatment. This new source might thus serve in the future as a useful surrogate for engine exhaust emissions and help to improve calibration procedures of common aerosol instruments. Copyright © 2018 The Author(s). Published with license by Taylor & Francis Group, LLC